2001
DOI: 10.1007/s005950170034
|View full text |Cite
|
Sign up to set email alerts
|

Successful Surgical Treatment of a Ruptured Abdominal Aortic Aneurysm Without Homologous Blood Transfusion in a Jehovah's Witness: Report of a Case

Abstract: We report herein the case of a 47-year-old woman of the Jehovah's Witness faith in whom Y-grafting for a ruptured abdominal aortic aneurysm was successfully performed without a homologous blood transfusion. We used a Cell Saver (Haemonetics, Braintree, MA. USA) red cell salvaging device and an aortic occlusion balloon catheter, and performed gentle and minimal dissection during the operation. Postoperatively. the patient was kept heavily sedated and required hypothermic therapy for only 14h. We treated her sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…3), 56.1 mmHg in rAAA and 52.4 mmHg other types of patients in established hemorrhagic shock, among the 23 studies [10, 12, 22, 25, 2931, 34, 36, 40, 41, 44, 45, 47, 48, 52, 55, 58, 59, 62, 66, 71, 97, 104, 105, 111] reporting pre-REBOA and post-REBOA SBP values.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3), 56.1 mmHg in rAAA and 52.4 mmHg other types of patients in established hemorrhagic shock, among the 23 studies [10, 12, 22, 25, 2931, 34, 36, 40, 41, 44, 45, 47, 48, 52, 55, 58, 59, 62, 66, 71, 97, 104, 105, 111] reporting pre-REBOA and post-REBOA SBP values.…”
Section: Resultsmentioning
confidence: 99%
“…REBOA balloon occlusion times were adequately reported in 35 studies [10, 12, 23, 25, 26, 2934, 36, 3841, 4345, 47, 48, 55, 58, 62, 66, 6871, 82, 83, 97, 101, 104, 105]. Occlusion times within the zones of occlusion were described in 15 studies examining Zone I occlusion times, where 196 patients had a median occlusion time of 58.4 min.…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, this patient had normal blood lactate levels, despite an extremely low arterial oxygen content of 2·3 mL dL −1 (one tenth of normal levels) upon admission to our hospital. Several successful cases with extremely low Hb levels [nadir Hb <3 g dL −1 (Baker et al, 1998;Namura et al, 2001), nadir <2 g dL −1 (Brimacombe et al, 1991;Schalte et al, 2005)] have been reported. It was shown previously that in patients who declined transfusion with low nadir Hb levels (Hb <8·0 g dL −1 ), the occurrence of patients with nadir Hb levels <2·0 g dL −1 was rare (frequency 0-2·3%) (Carson et al, 2002;Shander et al, 2014).…”
Section: Dear Sirmentioning
confidence: 99%
“…Although complex surgery associated with major blood loss has conventionally been contraindicated in Jehovah’s Witness patients, such procedures have been successfully performed when a multidisciplinary approach has been taken to conserve blood. Numerous case reports and articles have described the management of Jehovah’s Witness patients with severe blood loss or undergoing surgical procedures 1–6 . The aims of interventions are to minimize blood loss, maximize blood production, regulate blood volume and maintain normovolemia, increase the oxygen‐carrying capacity of the blood, and decrease the metabolic rate.…”
Section: Introductionmentioning
confidence: 99%